Combination of Ganoderma lucidum pellets and activated dolomite for decolourisation and cod removal of industrial textile wastewater in batch bioreactor / Afnan Ahmadi Zahuri - Afnan Ahmadi , Zahuri (2024)
The revolutionary textile industry with the “fast fashion” trend is meeting the consumers’ demands in more affordable ways. Yet, this convenience arises at an extensive environmental cost, notably manifested through the issue of textile wastewater worldwide. Although Malaysia has established good technology in treating textile wastewater, the government and industry players are shifting towards more sustainable and greener efforts nowadays. In this study, utilising living Malaysian Ganoderma lucidum mycelial pellets and activated dolomite has explored the synergy between bioaccumulation and physisorption as an alternative for textile wastewater treatment. The adsorbents were produced and introduced into industrial textile wastewater to find the optimal treatment conditions. The morphology, adsorption characteristics, and antimicrobial activity of the adsorbents were studied. Both adsorbents are capable of removing colours and reducing chemical oxygen demand (COD) value by 77.8% and 75% within 48 hours, respectively. The Langmuir and Freundlich models were used to study the adsorption capability. Additionally, antimicrobial activities can be observed from mycelial pellets and activated dolomite. The synergetic treatment by Ganoderma lucidum mycelial pellets and activated dolomite has immense potential in future wastewater treatment technology to obtain cleaner water.